Democracy's beginning the Athenian story - Mitchell, Thomas N. 1939- (Yale University Press, 2015)
The first democracy, established in ancient Greece more than 2,500 years ago, has served as the foundation for every democratic system of government instituted down the centuries. In this lively history, author Thomas N. Mitchell tells the full and remarkable story of how a radical new political order was born out of the revolutionary movements that swept through the Greek world in the seventh and sixth centuries B.C., how it took firm hold and evolved over the next two hundred years, and how it was eventually undone by the invading Macedonian conquerors, a superior military power. Mitchell's superb history addresses the most crucial issues surrounding this first paradigm of democratic governance, including what initially inspired the political beliefs underpinning it, the ways the system succeeded and failed, how it enabled both an empire and a cultural revolution that transformed the world of arts and philosophy, and the nature of the Achilles heel that hastened the demise of Athenian democracy